Monte Carlo investigation of critical properties of ferroelectric films: The DIFFOUR Hamiltonian framework - Laosiritaworn Y. (2014)
In this work, Monte Carlo simulation was used to investigate the ferroelectric films behavior using the DIFFOUR Hamiltonian. The considered electric dipole directions were considered to range from 2 to 14 directions, in representing various domain structures. Metropolis algorithm was used to extract the polarization, the susceptibility, and critical behavior for each domain structure. It was found that the critical temperature increases with increasing the films thickness due to stronger ferroelectric interaction, but reduces in structure with more possible dipole-switching directions due to lower energy barrier. Scaling of the critical temperature with films thickness and its shifting exponent are reported. Copyright © Taylor & Francis Group, LLC.